2019
DOI: 10.1088/1361-6528/aaef13
|View full text |Cite
|
Sign up to set email alerts
|

Modulated electrochemical oxygen evolution catalyzed by MoS2 nanoflakes from atomic layer deposition

Abstract: Electrochemical water splitting into H 2 and O 2 has attracted wide attention owing to the urgent need for clean and renewable energy sources. However, the scarcity and high-cost limit the large-scale application of noble metal catalysts such as IrO 2 and RuO 2 . In this work, as a lowcost catalyst for the electrochemical O 2 evolution reaction (OER), MoS 2 nanoflakes were obtained by atomic layer deposition (ALD) using MoCl 5 and H 2 S on carbon fiber paper surface. According to the results of electrochemical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 62 publications
(58 reference statements)
0
20
0
Order By: Relevance
“…Nevertheless, these studies have shown highly promising results that are comparable to the best MoS 2 and other nonplatinum metal OER catalysts reported in literature (see refs. [190,331] and references therein), therefore motivating further studies on the subject.…”
Section: Electrocatalytic Water Splitting: Oxygen Evolution Reactionmentioning
confidence: 99%
See 3 more Smart Citations
“…Nevertheless, these studies have shown highly promising results that are comparable to the best MoS 2 and other nonplatinum metal OER catalysts reported in literature (see refs. [190,331] and references therein), therefore motivating further studies on the subject.…”
Section: Electrocatalytic Water Splitting: Oxygen Evolution Reactionmentioning
confidence: 99%
“…Biosensor [188] 400 tens of nm rough film (cryst.) Biosensor [189] 450 ≈5-50 nm rough films (≈10-20 nm) OER [190] 390-470 1-3 ML flakes (≈50-400 nm) 4-5 ML films (≈400 nm) - [119] 250-325 20−70 nm rough films (10-100 nm) HER 2017 [191] 150-300 5-50 nm rough films (10-300 nm) LIB, NIB [192] 250-300 ≈5-70 nm rough films (10-50 nm) PEC [193] 250 ≈20 nm rough film (≈10-20 nm) PEC [194] 250 ≈7-30 nm rough film (≈10-30 nm) PEC [195] 200-420 1-8 ML films (10-25 nm) FET [196] MoCl 5 + S(SiMe 3 ) 2 375 (800, S) 8 ML film (as-dep. amorp., ann.…”
Section: Atomic Layer Deposition Processes For 2d Metal Dichalcogenidesmentioning
confidence: 99%
See 2 more Smart Citations
“…[70] MoS 2 layered nanoflakes were prepared using MoCl 5 and H 2 S on carbon fiber paper (CFP) at 450 °C. [71] The MoS 2 uniformly covered the CFP surface without bulk accumulation and its density increased with increasing number of ALD cycles. The film was S deficient (S/Mo ratio was 1.71) and amorphous (or had a low crystallinity).…”
Section: Direct Synthesis Of 2d Tmcs By Th-aldmentioning
confidence: 93%